Native and Nonnative Perception of Western Andalusian Spanish /S/ Aspiration in Quiet and Noise - Del Saz-Caracuel, M (Cambridge University Press, 2019)
Many college students set out on Study Abroad Programs to other countries in which the variant of the foreign language spoken in the region differs from the variant to which learners have been exposed. This study explores the perception of L2 Western Andalusian Spanish aspiration of word-final /s/ by L1 American English listeners, in relation to their length of exposure to the L2 in quiet conditions and to their competence level in the L2 in noisy conditions. Results indicate that perception drops in adverse conditions, particularly for listeners in their intermediate stages of learning. Proficient listeners perception also suffers with respect to native listeners performance at lower signal-to-noise ratios. For all listeners, native and nonnative, standard features are best identified, whether in quiet or noise. Copyright © Cambridge University Press 2019.